Change in Lifestyle through Health Promotion Program without Face‐to‐Face Intervention in a Large‐scale Japanese Enterprise. Issue 2 (28th June 2013) - Haruyama, Yasuo; Fukuda, Hiroshi; Arai, Tomoe; Muto, Takashi
Abstract : Change in Lifestyle through Health Promotion Program without Face‐to‐Face Intervention in a Large‐scale Japanese Enterprise: Yasuo HARUYAMA, et al . Department of Public Health, Dokkyo Medical University School of Medicine— Objective: The aim of this study was to assess the effect of a health promotion program with 2−3‐month Internet or printed material support without a face‐to‐face intervention at a largescale worksite. Methods: An uncontrolled intervention was conducted. In 2005, 22, 429 employees underwent a health check‐up and a lifestyle assessment. In 2006, 2, 096 employees were recruited to participate in an intervention group (IntG), and the remaining 20, 228 employees were allocated to a control group (ConG). After one‐year follow‐up, 1, 888 employees in IntG and 15, 474 employees in ConG were analyzed by Breslow's lifestyle index, overall prevalence of cardiovascular risk (OPCR) and 10% 10‐year risk based on cardiovascular risk factors in 2007. Results: Breslow's lifestyle index (over 5 points) in IntG showed a higher OR (1.13 with a 95% CI of 1.01−1.26) than that in ConG. Compared with those with a poor lifestyle, the subjects who had maintained or improved their lifestyle showed a lower OPCR (OR 0.88, 95% CI 0.79−0.97; OR 0.84, 95% CI 0.74−0.95 [ p for trend=0.003]) and 10% 10‐year risk trend (OR 0.38, 95% CI 0.31−0.47; OR: 0.29, 0.22−0.37 [ p for trend <0.001]). Conclusion: The present study showed that there was a modest lifestyle behavior change using a program without face‐to‐face contact. The employees who maintained and improved their lifestyle had a lower OPCR and 10% 10‐year risk. Future study should increase the number of employees actively attempting to improve their lifestyles at a worksite.